Pelatihan dan Pendampingan Aparatur Desa Bira dalam Penyusunan Laporan Keuangan yang Berbasis Akuntabilitas - Surianto, Nurul Maghfirah; Ryketeng, Masdar; Azisah, Andi Nurul; Nadhiyah Putri Wahdana; Muflikhah, Itsna (Rahmatan Lil 'Alamin Journal of Community Services, 2026)
This community service initiative was prompted by the limited capacity of village officials to prepare financial reports that are accountable, transparent, and in accordance with the principles of good governance. This situation has the potential to lead to errors in village financial recording and reporting, which in turn lowers public trust. Therefore, this initiative aims to enhance the understanding and skills of Bira Village officials in preparing accountability-based financial reports. The methods employed include training, on-site mentoring, and an assessment of participants’ ability to prepare village financial reports. Training is delivered through sessions covering principles of accountability, village financial reporting standards, and systematic report preparation practices. Subsequently, intensive mentoring was conducted to ensure participants were able to implement the knowledge gained. The results of the activity showed a significant improvement in the understanding and skills of village officials in preparing financial reports that are more orderly, transparent, and accountable.